98.3k views
0 votes
H(x) = x + 1 k(x) = x - 2 (h + k)(2) =​

User Andy Dent
by
5.1k points

2 Answers

3 votes

Answer:it’s 5

Explanation:

because it is

User Colriot
by
5.4k points
4 votes


h(x) = x + 1


k(x) = x - 2

_________________________________


(h + k)(x) = h(x) + k(x)


(h + k)(x) = (x + 1) + (x - 2) \\


(h + k)(x) = x + 1 + x - 2


(h + k)(x) = 2x - 1


(h + k)(2) = 2(2) - 1


(h + k)(2) = 4 - 1


(h + k)(2) = 3

_________________________________

And we're done.....♥️♥️♥️♥️♥️

User JohnPristine
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.